IMPLEMENTATION OF GOOD GOVERNANCE TO IMPROVE THE PERFORMANCE OF VILLAGE GOVERNMENTS - Yesi Mutia Basri; Tusanti Igus Findayani; Arumega Zarefar (Jurnal Akuntansi, 2021)
Law No. 6 of 2014 concerning villages is the starting point for villages to manage their government independently. However, in the management of government, many villages are still weak in implementing good governance, so that it has an impact on their performance. This study specifically wants to examine the role of good governance in improving the performance of village governments. This study examines the principles of good governance, transparency, accountability, community participation and fairness towards village government performance. The population of this research is the village government in the Meranti Islands Regency. The sampling technique used was area sampling, so that a total sample size of 31 villages was obtained in Tebing Tinggi, Tebing Tinggi Barat and Rangsang Barat, Meranti Islands Regency. Data was collected through a survey by distributing questionnaires to respondents consisting of the village head, village secretary, head of financial affairs and head of general affairs. The analytical method used in this study is multiple regression analysis with the help of SPSS version 23.0. The results showed that transparency, accountability, community participation and justice had a positive effect on the performance of the village government.  This indicates that increased transparency, accountability, community participation and justice will improve the performance of village government in Meranti Regency. The research supports the stewardship theory that the village government will act to fulfill the interests of the village community.